(untitled) (Anais do Congresso Brasileiro de Processo Coletivo e Cidadania, 2022)
This article aims to reflect the institute’s prevalence of the negotiated over the legislated, resulting from the inclusion of Art. 611-A of the CLT by Law No. 13,467/2017 in the Consolidated Labor Laws. As well as the role of trade unions in balancing negotiations in the face of uncertainty of the material limits of these negotiations. Still, the violation of fundamental rights of the most beneficial norm and the dignity of the human person when the law gave permission for the hypersufiente to be able to negotiate their rights with the employer. The method adopted was analytical-deductive, using legal material, based on books, scientific articles, legislation and online sites that were analyzed in the preparation of the research, aiming to bring to light controversial issues, having as its motto the prevalence of the negotiated over the legislated.